PROBLEMATIKA TEMPAT PEMIDANAAN TERHADAP PELAKU ANAK DALAM PUTUSAN HAKIM (STUDI PUTUSAN NOMOR 67/PID.SUS-ANAK/2021/PN.BTM): Problems of the place of punishment for child offenders in the Judge’s decision (Study of Decision No. 67/Pid.Sus-Anak/2021/PN.Btm) - Victory Hengky Parinussa; Setiyono (Reformasi Hukum Trisakti, 2026)
Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law) emphasizes that the Special Children’s Development Institution (Lembaga Pembinaan Khusus Anak/LPKA) is the designated place for implementing criminal punishment for children in conflict with the law. This provision aims to guarantee the protection of children’s rights, ensure separation from adult offenders, and support guidance and rehabilitation. The problem is, in judicial practice shows that some court decisions do not explicitly include LPKA in the verdict, although it is mentioned in the legal considerations, as reflected in the Batam District Court Decision Number 67/Pid.Sus-Anak/2021/PN.Btm. This study aims to analyze the conformity between the normative provisions of the SPPA Law and their application in the decision. The research employs a normative juridical method with a descriptive approach through document studies of statutory regulations, court decisions, and relevant legal literature. The analysis is conducted qualitatively using deductive reasoning. The findings indicate that the omission of LPKA in the verdict creates legal uncertainty and may undermine the principles of child protection and the objectives of the Juvenile Criminal Justice System, which emphasize rehabilitation and the best interests of the child.